PENGARUH INDEPENDENSI, KOMPETENSI, DAN SENSITIVITAS ETIKA PROFESI TERHADAP PRODUKTIVITAS KERJA AUDITOR EKSTERNAL (STUDI KASUS PADA AUDITOR PERWAKILAN BPK RI PROVINSI KALIMANTAN TIMUR) - Hari Adi Suwondo; Sukisno S Riadi; Siti Maria (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the effect of Independence, Competence and Sensitivity Professional Ethics of the auditor's work productivity. This research is a quantitative survey approach. The sampling technique using a sample population that took the entire population as a sample. The independent variables consist of Independence (X1), Competence (X2) Sensitivity Ethics (X3), while the dependent variable adala auditor labor productivity (Y), Methods Data were analyzed using multiple linear regression with F test and t test. The results showed that the variable Independence (X1), Competence (X2) and Sensitivity Ethics (X3) simultaneously significant effect on the productivity of auditor BPK RI Representative of East Kalimantan Province.Keywords: Independence, competence, sensitivity Ethics and Work Productivity